Revision of the Malagasy lanternfly genus Belbina Stål, 1863, with two new species (Hemiptera: Fulgoromorpha: Fulgoridae) - Constant, Jérôme (European Journal of Taxonomy, 2014)
The Malagasy genus Belbina Stål, 1863 (Hemiptera: Fulgoridae) is revised, transferred from the Enchophorinae Haupt, 1829 to the Aphaeninae Blanchard, 1847, and two new species, B. bourgoini sp. nov. and B. laetitiae sp. nov., are described. The genus Cornelia Stål, 1866 is proposed as a junior synonym of Belbina. The following new combinations are proposed: Belbina bergrothi (Schmidt, 1911) comb. nov. and B. nympha (Stål, 1866) comb. nov. The combination Belbina foliacea Lallemand, 1950 is restored. Aphana madagascariensis Westwood, 1851 is redescribed, transferred to Belbina and the new combination B. madagascariensis (Westwood, 1851) comb. nov. is proposed. Belbina vicina Lallemand, 1959 is proposed as a junior synonym of B. falleni Stål, 1863 and Cornelia atomaria (Brancsik, 1893) as a junior synonym of Belbina nympha (Stål, 1866). Neotypes are designated for B. madagascariensis (Westwood, 1851) and B. servillei (Spinola, 1839). The genus now comprises 12 species from Madagascar. A list of diagnostic characters, an identification key, illustrations of the male genitalia and distribution maps are provided. The falleni+ species group is defined based on characters of the male genitalia and contains the following 5 species: B. bloetei Lallemand, 1959, B. falleni Stål, 1863, B. laetitiae sp. nov., B. lambertoni Lallemand, 1922 and B. pionneaui Lallemand, 1922.